Pembatalan Perkawinan Akibat Nikah Diluar Perwalian di Pengadilan Agama Sungguminasa Kelas Ib: Studi Putusan Nomor 055/Pdt.Gugatan/2020/Pengadilan Agama.Sgm. - Nurjannah, Nurjannah; Ridwan, Muh. Saleh; Abdillah, Abdillah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Marriage has important conditions to be fulfilled, so that the non-fulfillment of conditions in marriage can result in the cancellation of marriage including in terms of guardianship. The main point of this study is how the annulment of marriage due to marriage outside guardianship in the case of decision number 055/PNdt.Lawsuit/2020/Religious Court.Sgm regarding the annulment of marriage due to marriage outside guardianship. This study aims to determine the annulment of marriage due to marriage outside guardianship in the case of decision number 055/Pdt.Gugaltaln/2020/Religious Court. This type of research uses qualitative research with the Field Reseach method. This research is carried out directly in the field using a qualitative descriptive approach, namely by exploring what will be thoroughly researched. The processed data is sourced from written literature and interviews with judges and people within the scope of the court. The results showed that performing a marriage outside of guardianship or without an ordinary guardian resulted in the marriage being invalid, so harmony and conditions in carrying out worship need to exist to determine the validity or invalidity of a worship. In the case of decision number 055/Pdt.Gugaltaln/2020/Religious Court.Sgm, the tribunal is of the opinion that the petition of the petitioner (father) has been proven according to law in accordance with the articles mentioned above so that the marriage in question should be annulled. The implications of this study presumably in the implementation of marriage need to be considered regarding the harmony and requirements of a marriage. In checking the identity of the prospective bride and groom not only prioritizes the truth administratively, but efforts are made to be able to check the field and guidance to the community, so that in carrying out marriage or marriage there are no rules that are violated.